2022
DOI: 10.47836/mjmhs.18.s15.44
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Associated With Fragility Fracture Among Older Adults With Fragility Fracture: A Systematic Review

Abstract: Aim: To investigate risk factors of fragility fractures among older people. Data Sources: The electronic databases employed were PubMed, Science Direct, and Google Scholar from 2016 to December 2021. Review Method: The methodological quality of the studies was assessed using the National Institutes of Health (NIH) Quality Assessment Tool for Observational Cohort and Cross-sectional study. Two independent reviewers screened total 147 articles. Results: Twelve studies were finally included in this review that co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Handgrip strength (HGS) is an important health indicator for older adults, as its lower value is associated with adverse outcomes such as fragility and falls [ 1 , 2 ]. As described in a review study, a lower HGS is positively associated with the risk of fragility independently with various aging markers and physical functioning [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Handgrip strength (HGS) is an important health indicator for older adults, as its lower value is associated with adverse outcomes such as fragility and falls [ 1 , 2 ]. As described in a review study, a lower HGS is positively associated with the risk of fragility independently with various aging markers and physical functioning [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Handgrip strength (HGS) is an important health indicator for older adults, as its lower value is associated with adverse outcomes such as fragility and falls [ 1 , 2 ]. As described in a review study, a lower HGS is positively associated with the risk of fragility independently with various aging markers and physical functioning [ 1 ]. A recent prospective study showed that a greater HGS was associated with better functional outcomes after 1-year follow-up among fragility hip fracture patients [ 3 ].…”
Section: Introductionmentioning
confidence: 99%
“…The concept of 'fragility fracture' refers to so-called 'low-energy trauma' resulting in a fracture due to factors often associated with advanced age. Hip fracture is the most significant fragility fracture (Abd Kahar et al, 2022). The mortality rate is high and increases with age (Kristensen & Kehlet, 2018).…”
Section: Introductionmentioning
confidence: 99%